Teacher Quality, Facilities, and Cost: A Discourse Analysis of Quora Narratives on Public vs. Private Schools in Indonesia - Muhammad Saefulloh (Universitas 17 Agustus 1945 Surabaya, 2026)
This study examines public perceptions of public versus private schools in Indonesia using user-generated content from Quora. Parents face a difficult decision when choosing between Indonesia's large number of public (7,396) and private (7,049) senior high schools. Thirty answers to the question